Protective head-cooling during cardiac arrest and cardiopulmonary resuscitation: the original animal studies - Eric W. Brader; Dietrich Jehle; Michael Mineo; Peter Safar (MDPI AG, 2010)
Prolonged standard cardiopulmonary resuscitation (CPR) does not reliably sustain brain viability during cardiac arrest. Pre-hospital adjuncts to standard CPR are needed in order to improve outcomes. A preliminary dog study demonstrated that surface cooling of the head during arrest and CPR can achieve protective levels of brain hypothermia (30°C) within 10 minutes. We hypothesized that protective head-cooling during cardiac arrest and CPR improves neurological outcomes. Twelve dogs under light ketamine-halothane-nitrous oxide anesthesia were arrested by transthoracic fibrillation. The treated group consisted of six dogs whose shaven heads were moistened with saline and packed in ice immediately after confirmation of ventricular fibrillation. Six control dogs remained at room temperature. All 12 dogs were subjected to four minutes of ventricular fibrillation and 20 minutes of standard CPR. Spontaneous circulation was restored with drugs and countershocks. Intensive care was provided for five hours post-arrest and the animals were observed for 24 hours. In both groups, five of the six dogs had spontaneous circulation restored. After three hours, mean neurological deficit was significantly lower in the treated group (P=0.016, with head-cooled dogs averaging 37% and the normothermic dogs 62%). Two of the six head-cooled dogs survived 24 hours with neurological deficits of 9% and 0%, respectively. None of the control group dogs survived 24 hours. We concluded that head-cooling attenuates brain injury during cardiac arrest with prolonged CPR. We review the literature related to the use of hypothermia following cardiac arrest and discuss some promising approaches for the pre-hospital setting.